Characteristic flavor metabolic network of fish sauce microbiota with different fermentation processes based on metagenomics - Han, Jiarun; Kong, Tao; Jiang, Jialan; Zhao, Xin; Zhao, Xilian; Li, Ping; Gu, Qing (Frontiers in Nutrition, 2023)
This article purposed to discuss the connection between microbiota and characteristic flavor of different fish sauces (Natural fermentation (WQ), koji outdoor fermentation (YQ), heat preservation with enzyme (BWE), and heat preservation with koji (BWQ)) at the early (3 months) and late stage (7 months). A total of 117 flavor compounds were determined according to SPME-GC–MS analysis. O2PLS-DA and VIP values were used to reveal 15 and 28 flavor markers of different fish sauces at 3 and 7 M of fermentation. Further, the possible flavor formation pathways were analyzed using metagenomic sequencing, and the key microbes associated with flavor formation were identified at the genetic level. The top 10 genera related to flavor generation, such as Lactobacillus, Staphylococcus, Enterobacter, etc., appeared to play a prominent part in the flavor formation of fish sauce. The difference was that only BWQ and BWE groups could produce ethyl-alcohol through amino acid metabolism, while YQ, BWE and BWQ groups could generate phenylacetaldehyde through the transformation of Phe by α-ketoacid decarboxylase and aromatic amino acid transferase. Our research contributes to clarifying the various metabolic roles of microorganisms in the flavor generation of fish sauce.